Election poster persuasion: attitude formation in the void - Schott, Malte; Wolf, Jule (Social psychology, 2018)
We examined the effect of presenting unknown policy statements on German parties’ election posters. Study 1 showed that participants inferred the quality of a presented policy from knowledge about the respective political party. Study 2 showed that participants’ own political preferences influenced valence estimates: policy statements presented on campaign posters of liked political parties were rated significantly more positive than those presented on posters of disliked political parties. Study 3 replicated the findings of Study 2 with an additional measure of participants’ need for cognition. Need for cognition scores were unrelated to the valence transfer from political parties to policy evaluation. Study 4 replicated the findings of Studies 2 and 3 with an additional measure of participants’ voting intentions. Voting intentions were a significant predictor for valence transfer. Participants credited both their individually liked and disliked political parties for supporting the two unknown policies. However, the credit attributed to the liked party was significantly higher than to the disliked one. Study 5 replicated the findings of Studies 2, 3, and 4. Additionally, participants evaluated political clubs that were associated with the same policies previously presented on election posters. Here, a second-degree transfer emerged: from party valence to policy evaluation and from policy evaluation to club evaluation. Implications of the presented studies for policy communications and election campaigning are discussed.
Gesehen am 23.04.2020